If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -6 = 4(3x + -1) Reorder the terms: -6 + 11x = 4(3x + -1) Reorder the terms: -6 + 11x = 4(-1 + 3x) -6 + 11x = (-1 * 4 + 3x * 4) -6 + 11x = (-4 + 12x) Solving -6 + 11x = -4 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -6 + 11x + -12x = -4 + 12x + -12x Combine like terms: 11x + -12x = -1x -6 + -1x = -4 + 12x + -12x Combine like terms: 12x + -12x = 0 -6 + -1x = -4 + 0 -6 + -1x = -4 Add '6' to each side of the equation. -6 + 6 + -1x = -4 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = -4 + 6 -1x = -4 + 6 Combine like terms: -4 + 6 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| 6(x+2)=12x | | p-c=r | | -4(2x-1)+10=9-3x | | 3xsquared=2x+7 | | 49t^3+5t=42t^2 | | 15m^4+114m^4=189 | | 5x-4-3x+15= | | 5(x^2-1)=50 | | y-7+14y=13 | | 6x-5=3n+10 | | (3+2x)(3.25+2x)=15 | | 3x-12=-12+3x | | c-d=f | | 10x/x-6-60/x-6 | | 27x^2/3 | | =7x+5(1-x) | | 6(q-3)=-4(q+2) | | 5=10z+2(-7/2z-1) | | 2x-2=6x+1 | | 2p=km-t | | 3(x-4)=-1/2(24-6x) | | x-(5-3x)=7x*4 | | -5p=100 | | (19x-5)+(x+7)= | | 72*3/2 | | 1.5+2.5x+x=25 | | 3x^3-6x^2-75x+150=0 | | 5/2x=35-x | | 4r-8=24 | | -2=4y+x | | 5=13z-(z-1) | | 7x+2(7x+16)=179 |